Effects of reaction conditions and organic sulfur compounds on coke formation and HZSM-5 catalyst performance during jet propellant fuel (JP-8) cracking. (1st January 2020) - Kim, Sungtak; Sasmaz, Erdem; Pogaku, Ravindra; Lauterbach, Jochen
Abstract: Coke formation and catalytic performance under various conditions, such as reaction period, temperature, presence of carrier gas and organic sulfur compounds in the feed, were investigated for JP-8 cracking over HZSM-5 catalysts. The spent HZSM-5 catalysts were characterized by N2 adsorption/desorption, X-ray powder diffraction (XRD), Fourier-transform infrared spectroscope (FT-IR), Temperature programmed oxidation (TPO), and X-ray photoelectron spectroscopy (XPS). A significant loss of surface area and pore volume appeared in the initial period of the cracking reaction, owing to coke formation. Complex, aromatic structured coke formed and deposited on the surface the HZSM-5 catalyst. This resulted in high carbon content, carbon burn-off at higher temperatures, and a change in morphology to less well-defined shapes. As the reaction temperature increased, the aromaticity of the coke species increased, thereby resulting in the coke species having more carbon content and a lower H/C ratio. Furthermore, the absence of a carrier gas gave rise to faster catalyst deactivation and lower LPG yield. Surrogate JP-8 fuel experiments revealed that the aromatic sulfur compounds in the feed do not degrade the catalytic activity by sulfur poisoning, but rather by accelerated coke formation.